High-Speed Photonic Processing for Communications and Security Applications - Τσέλιος, Χρήστος (Πανεπιστήμιο Πελοποννήσου, 2025)
Today's digital landscape is undergoing a profound transformation, driven by the convergence of 5G, edge computing, and artificial intelligence (AI). As technology accelerates, the demand for faster, larger, and more secure data transfers is becoming paramount. At the same time, the growing complexity of AI systems calls for innovative solutions like neuromorphic computing, which can efficiently manage real-time data processing and complex decision-making tasks. This shift has led to a growing interest in multifunctional platforms, capable of addressing both the speed and security challenges posed by modern communication systems while advancing the capabilities of AI-driven technologies. Optoelectronic technologies, particularly Vertical-Cavity Surface-Emitting Lasers (VCSELs), have significantly enhanced communication infrastructure by enabling high bandwidth, energy efficiency, and cost-effectiveness. However, the emergence of spin-VCSELs marks a transformative advancement. Spin-VCSELs leverage the conservation of angular momentum to control the helicity of emitted light through the injection of spin-polarized carriers. Operating at room temperature and without the need for external magnetic fields, these devices not only enable innovative applications, such as ultrafast data transmission and advanced encryption methods, but also provide fundamental insights into the interplay between spin physics and optoelectronics. In this thesis, Quantum-Dot (QD) spin-VCSEL devices are investigated to demonstrate how they can offer crucial solutions to the aforementioned challenges. Firstly, the ability to perform precise polarization control through the rich polarization behavior ranging from spin amplification to polarization chaos is presented. An extensive analysis of its nonlinear dynamic characteristics is conducted, discussing how different dynamical regimes can be exploited for novel applications. The optimization of the chaotic regime unveils parallel wideband complex chaos generation at 90 GHz and random number generation at 240 Gb/s, capable of passing all statistical tests in the NIST test suite. The intrinsic advantages of both the active material and the device are leveraged to perform polarization-enabled ultrafast optical communication systems, aiming toward terabit-per-second (Tb/s) data transmission with increased modulation efficiency. These principles are also employed for advanced computing tasks such as neuromorphic XOR operation and spike rate coding for digital images, enabling efficient processing of complex AI workloads through neuromorphic computing. Finally, this thesis discusses the key milestones achieved and highlights their contribution to the broader field. Future research directions are outlined, ranging from quantum communication systems to advanced neuromorphic photonic architectures, with particular emphasis on the practical realization of these systems and strategies to overcome current technological limitations.
Keywords: spin-vcsel; polarization dynamics; chaos; data transmission; security